REGRESSION ANALYSIS AND GIS METHODS FOR ASSESSMENT OF THE PLAGUE EPIZOOTIC ACTIVITY OF KAZAKH NATURAL PLAGUE FOCI - N. .. Niyazbekov; Z. .. Abdeliyev; Z. .. Sagiyev; A. .. Matzhanova; A. .. Abdrazakova; B. .. Aysauytov; M. .. Balibayev; N. .. Toksanbayeva; Sh. .. Ibrayeva; A. .. Yermakhanov; M. .. Burambayeva; S. .. Zhadyrassyn; et al. (Acta Biomedica Scientifica, 2014)
The plague natural foci of Kazakhstan are a complicated system of relations between the plague microbe, warm-blood host and vector. The complex approaches used for study of the processes of the plague epizooty and prognosis it. Use of computerized programs with the classic methods of study helps to process the data in time and space. For epidemiological and epizootological analysis the passport data of the strains Y. pestis isolated by Zhosaly Anti-plague Station of the Republic of Kazakhstan in 1990-2012 were processed. The Anti-plague Station carries out the epizootic study of the landscape and epizootology regions as the North Qizilqum, East Karakum, and West part of Aryskum-Dariyalyktakyr. From 1990 to 2012 there were 295 plague strains isolated, 57 % of them were isolated from rodents, and 49,3 % of them were isolated from vectors (ticks and fleas). The passport data for 1990-2011 of three mentioned above landscape and epizootology regions were processed by STATA 12 program; and the regression models of the North Qizilqum and East Karakum were created. The model shows that the plague epizooty activity has been declining by the years. The second model shows that the plague activity in the North Qizilqum has been increasing by the years. Also the passport data of the strains Y. pestis isolated in two natural plague foci of Central Asia desert plague focus as Qizilqum and Aryskum-Dariyalyktakyr natural foci were processed by ArcGIS 10. The regression analysis and modeling in ArcGIS 10 give the opportunities for carrying out of spatial and temporal characteristics of conditions of epizootic activities of the natural plague foci, for detection more possible regions where people livestock as camels can be infected with plague and for prevention of infection of people during their activities. Application of this analysis in the complex of epizootic and epidemiological analysis gives the possibility to prognosis of possible plague epidemic complications and make remote prognosis for carrying out of the prophylaxis measurements under the influences of anthropogenic transformation of the foci, social and climatic factors and can help to survey the foci and protect the population who live there. Use of the regression analysis in the epidemiological and epizootological monitoring of the plague in the natural plague foci can help to prognosis the dynamics of the plague epizooty in the foci and detect a correlation between the microbe, vector, and host of the plague.